Efektivitas Beberapa Isolat Trichoderma Sp. Terhadap Keterjadian Penyakit Bulai yang Disebabkan oleh Peronosclerospora maydis dan Pertumbuhan Tanaman Jagung (Zea mays) - Ivayani Ivayani; Faris Faishol; Joko Prasetyo; Muhammad Nurdin (Politeknik Negeri Lampung., 2018)
Corn (Zea mays) is one of the important cereals crops as the source of food, animals feed or energy. The corn produces has decreased by year to year. One of the factors that decreased the corn produces is downy mildew. Downy mildew desease caused by Peronosclerospora maydis fungi that decreased the production until 90%. Application of antagonistic fungi is one of the alternative control. Trichoderma spp. is one of the antagonistic fungi that can suppress growth of another fungus. Trichoderma spp. is saprofit soil microorganism that naturally attacks pathogen fungi and has benefits for plant growth. This research was aimed to know the effect of some isolates of Trichoderma spp. for diseases of downy mildew and the effect for the plant growth. Treatments were prepared with Randomized Complete Block (RCB) with 7 treatments and 4 repetitions. The treatments consist are P0 (control), P1 (application Trichoderma viride isolate GDR), P2 (application Trichoderma harzianum isolate TRJ), P3 (application Trichoderma harzianum isolate TGN), P4 (application Trichoderma viride isolate NTF), P5 (application Trichoderma longibrachiatum isolate GRP) and P6 (application Trichoderma viride isolate KLN). The results of this research were Trichoderma viride isolate GDR, Trichoderma harzianum isolate TGN, Trichoderma viride isolate NTF and Trichoderma viride isolate KLN can be suppressed the disease incidence of downy mildew, but unaffected for the plants growth.